Application Of Social Inquiry Learning Model To Improve Socialproblem Solving Skills In Class V Of Integrated Islamic Sd Nurulikhwan Beach Mirrin - Supriadi; Yarsal, Dinda (Edumaniora : Jurnal Pendidikan dan Humaniora, 2022)
The learning method used in the learning process is an important key to student learning outcomes. Student learning outcomes are highly dependent on the learning methods used by the teacher. If the learning method used is boring, it cannot encourage students to become active students in learning. This is proven by the competence and skills possessed by students are still relatively low. And it does not encourage students to be active students in their learning. The problem formulation of this research is whether through the Social Inquiry Learning model to Improve Social Problem Solving Skills for Students of Class V Integrated Islam Nurul Ikhwan Pantai Cermin? The purpose of this study is to provide an overview of the learning implementation plan which was compiled using the social inquiry learning model in class V of Integrated Islam Nurul Ikhwan Pantai Cermin. Applying the Inquiry model to the fifth grade students of Integrated Islam Nurul Ikhwan Pantai Cermin in social studies learning. Improve the ability to work together and student learning outcomes in the classroom by using the Inquiry learning model in the social problem solving skills of students in the fifth grade of Integrated Islam Nurul Ikhwan Pantai Cermin. This study used 24 students as a sample of 120 students. Data collection is done by holding a pretest and posttest learning outcomes. The results showed that the teacher's activity in teaching using the social inquiry learning model showed increasing results.